Intra-household allocation of resources: inferences from non-resident fathers' child support payments - John Ermisch; Chiara Pronzato (Institute for the Study of Labor (IZA), 2006)
A large proportion of divorced and separated fathers form new partnerships. The new partner's preferences are not likely to put much weight on expenditures on the man's children from his previous union. Thus, his own and his partner's income would have different impacts on his child support payments if partners' relative incomes affect bargaining power in household decisions. This paper exploits within-father variation in the British Household Panel Survey (1991-2003) to estimate the impacts of intra-household income distribution on child support payments and the father's welfare. We find that a higher share of father's income in household income increases the probability of paying child support and its amount relative to household income.
urn:nbn:de:101:1-20080509168
Keywords: 330